2017
DOI: 10.14419/ijans.v6i1.7453
|View full text |Cite
|
Sign up to set email alerts
|

Work environment characteristics as perceived by nurses in Saudi Arabia

Abstract: Summary: The environment that contains; skilled nursing leadership who empowers their staff and improves their autonomy also allowing them to participate in the department and organizational policy, good nurse-doctor relationship, adequate resources and skilled mix staffing, play an essential role to enhance control over nursing practice. Aim: The aim of this study was to identify nurses' perception of work environment characteristics. Methodology: A cross-sectional descriptive research design was used through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
5
12
3
1
Order By: Relevance
“…The findings showed that the participants demonstrated a moderate level of positive perception regarding their work environment. These results are congruent with other studies conducted in Saudi Arabia (AlMoosa et al, 2020;Almuhsen et al, 2017), which showed moderate levels of satisfaction about work environment among multinational nurses. Concomitantly, international studies show comparable situations with no exceptions (Al-Hamdan, Manojlovich & Tanima, 2017;Özer et al , 2017;Ulusoy & Polatkan, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings showed that the participants demonstrated a moderate level of positive perception regarding their work environment. These results are congruent with other studies conducted in Saudi Arabia (AlMoosa et al, 2020;Almuhsen et al, 2017), which showed moderate levels of satisfaction about work environment among multinational nurses. Concomitantly, international studies show comparable situations with no exceptions (Al-Hamdan, Manojlovich & Tanima, 2017;Özer et al , 2017;Ulusoy & Polatkan, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…A four-point Likert scale was used to measure the items of the PES-NWI, from strongly disagree = 1 to strongly agree = 4. Previously, Almuhsen et al (2017) verified the validity and reliability of the scale, which vary from 0.87 to 0.96. In addition, this instrument was used in its original language.…”
Section: Practice Environment Scale Of the Nursing Work Index (Pes-nwi)mentioning
confidence: 84%
“…The overall total mean score of PES-NWI was moderate (M=2.9, SD=0.47), considering that majority of the respondents are staff nurses who routinely work at the bedside with patients, this relatively high mean score suggests favorability of practice environments. This result was in consistence with a Saudi study done by [14] who found a mean score of 2.44 for the total scale of PES-NWI.…”
Section: Discussionsupporting
confidence: 89%
“…In a study investigated the effect of leadership style on nurses' satisfaction among 89 nurses, use of the transformational leadership style significantly was correlated with higher nurses' job satisfaction in intensive care unit [13]. Another two studies done to identify nurses' perception of work environment characteristics using the Nursing Practice Environment questionnaire; one study was among 465 nurses [14] and the other study was among 1007 staff nurses found that nurses' perception of the work environment was moderately high.…”
Section: Introductionmentioning
confidence: 99%
“…These findings in the same line with the study of Al Moosa et al, (2020) also reported that nurses' perception of their work environment was not correlated with age, gender, marital status, but correlated with educational levels, and experience years. These findings disagreed with the study of Almuhsen et al, (2017) which indicate that staff nurses' work environment had significant relation with their education, and experience.…”
Section: Discussioncontrasting
confidence: 94%